The comparison of bacteriological flora between women with vulvar cancer and women with benign gynaecological diseases - Olejek, Anita; Nowowiejska-Wiewióra, Anna; Kozak-Darmas, Iwona; Kellas-Sleczka, Sylwia; Dyla, Łucja; Wiczkowski, Andrzej; Król, Wojciech (Menopause Review/Przegląd Menopauzalny, 2008)
Inflammation and infection have been linked to the pathogenesis of some cancers. For example, in cervical, liver and stomach cancer the relationships between chronic infections and carcinogenesis have been described. Vulvar cancer is rare in young women, and then it involves human papilloma virus. This kind of cancer occurs mostly in older women and there is a relationship between vulvar cancer and chronic bacterial infections. The aim of the study was to analyse the vaginal bacterial flora in women with vulvar cancer and in women with benign gynaecological diseases.